2014
DOI: 10.1159/000368883
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lower Concentrations of Hydrogen Sulfide with Atherosclerosis in Chronic Hemodialysis Patients with Diabetic Nephropathy

Abstract: Background/Aims: To explore the relationship between hydrogen sulfide (H2S) and uremic accelerated atherosclerosis (UAAS) in chronic hemodialysis patients with diabetic nephropathy (CHD/DN). Methods: A total of 36 CHD/DN and 32 chronic hemodialyzed non-diabetic patients with chronic glomerulonephritis (CHD/non-DN) were studied. Plasma H2S was measured with a sulfide sensitive electrode. Results: Plasma H2S in CHD/DN was significantly lower than that in CHD/non-DN patients. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
(45 reference statements)
3
30
0
Order By: Relevance
“…First, the precise method utilized for plasma H 2 S detection at present is controversial, due to technique differences, biological effects of H 2 S, diurnal fluctuations, and uncertain variations [36-38]. The spectrophotometric method employed in this paper could measure not only “free” H 2 S, but also protein-bound and acid-labile H 2 S [20].…”
Section: Discussionmentioning
confidence: 99%
“…First, the precise method utilized for plasma H 2 S detection at present is controversial, due to technique differences, biological effects of H 2 S, diurnal fluctuations, and uncertain variations [36-38]. The spectrophotometric method employed in this paper could measure not only “free” H 2 S, but also protein-bound and acid-labile H 2 S [20].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a reduction in hydrogen sulfide (H 2 S) has been suggested to play a vital role in diabetic vascular complications including diabetic nephropathy [29]. It was demonstrated that lower concentrations of H 2 S were responsible for the development and progression of diabetic nephropathy [36]. H 2 S generation in Type 2 diabetes with nephropathy is inversely associated with the CSE/CBS mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima-media thickness (IMT) was evaluated by carotid artery ultrasonography as described previously [16]. The presence of carotid plaque was defined as localized thickening (IMT ≥ 1.2 mm) that did not uniformly involve the whole wall of the carotid artery.…”
Section: Carotid Intima-media Thickness Measurementmentioning
confidence: 99%